(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
In this paper, the nature of spiritual or mystical experiences is discussed. An effort to sketch phenomenological criteria for differentiating these experiences from psychotic and depressive episodes is also provided, based on Jean-Luc Marion’s phenomenology and on Anthony Steinbock’s analysis. Key words Spiritual or mystical experiences, Dark Night of the Soul, mysticism, schizophrenia, depression, phenomenology, saturated phenomena, giveness. The worth of a man does not consist in the truth he possesses or thinks he possesses, but in the pains he has taken to attain that truth. For his powers are extended not through possession but through the search for truth. In this alone his ever-growing perfection consists. Possession makes him lazy, indolent, and proud. Gotthold Lessing When it comes to spiritual and in particular mystical experiences, psychologists and psychotherapists are trying to understand their nature and causes, and while doing this, it seems that they encounter cases of a ‘gray area’ which lead to a comparison: a comparison between a mystical experience and a psychotic episode or between a state of a Dark Night of the Soul and a depressive episode. Both types of experience seem to be extreme compared to the spectrum of ordinary human experiences and this, along with the peculiarity and complexity of their nature, has often led some scientists and philosophers to the conclusion that there is an eidetic similarity between these two kinds. The only way to ‘solve the problem’, to make a differentiation, seems to be the obscure criterion of ‘functionality’. In this paper, I will discuss the nature of spiritual or mystical experiences 122 and their right to exist as a legitimate functional human experience, based on Jean-Luc Marion’s phenomenology. I will further try to sketch phenomenological criteria for differentiating mystical experiences from psychotic and depressive episodes. This is an attempt to offer an additional angle with a view to hopefully enriching this complicated, on-going issue.